Cutting tool angle of lathe machine for different materials - Normawati, Mansor (2008)
Metal removals widely use industries. There are many factors need to be considers to investigate to produce a optimum cutting angle. Experimental were used a few of machine which is grinder machine, lathe machine, rough surface and angle measured. High speed steel will be used to create a tool bit. During the tests, the depth of cut and cutting speed were kept constant and each test was conducted with a sharp uncoated tool insert. The tool will be test on difference type of material which is aluminum and steel. Underlying of this research is based on the literature review. Harder material needs the tool bit angle closer upon to the wok piece. Less clearance angle need because more force required overcoming the existing force. As we know area will influence the performance of force. Larger area will reduce force. Steel and aluminum are employed as test material in order to check the effectiveness of the tool bit. First assumption for optimum cutting angle for both materials is base on recommended angle. Optimum angle for Steel is 12 degrees and for aluminum is 15 degrees. Both material use different angle because different in structure of grain and composition of the metal. Aluminum is ductile material and the steel is brittle metal. It not all steel is totally brittle because brittle depends on carbon present in the metal itself. According to the first expectation, chip will be form for steel is non-continuous because it ductile material and for aluminum is continuous chip because brittle. The results obtained when the process complete are steel required 9 degree angle and the chip produced is discrete and for aluminum the angle required is 18 degree and the chip produce is continuous. Experimental is applied to find the optimal angle for both metals.